Bio‐inorganic Hybrid Nanomaterials 2007
DOI: 10.1002/9783527621446.ch4
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Biomolecules on Mesoporous Structured Materials

Abstract: Various functional systems have been developed using artificially constructed structures and synthesized compounds, and the nanotechnology based on them has recently received much attention. However, current nanoscale technologies are still highly inferior to those seen in natural systems. The efficiency of the energy conversion that occurs in mitochondrial and photosynthetic systems far exceeds that obtained in artificial systems. A dog can smell and a bat can hear far more sensitively than most artificial se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 233 publications
(183 reference statements)
1
4
0
Order By: Relevance
“…Thus, the functionalization of silicabased adsorbents is necessary to achieve considerable adsorption uptake. It is frequently reported that the adsorption uptake of LH (as well as other amino acids) onto silica-based adsorbents is much lower than that on carbon mesoporous adsorbents (Goscianska et al 2014;Vinu et al 2005Vinu et al , 2006. In this work, we have clearly demonstrated that the proper functionalization of the surface layer of mesoporous silica can significantly enhance their adsorption efficiency.…”
Section: Adsorption Studiessupporting
confidence: 52%
See 3 more Smart Citations
“…Thus, the functionalization of silicabased adsorbents is necessary to achieve considerable adsorption uptake. It is frequently reported that the adsorption uptake of LH (as well as other amino acids) onto silica-based adsorbents is much lower than that on carbon mesoporous adsorbents (Goscianska et al 2014;Vinu et al 2005Vinu et al , 2006. In this work, we have clearly demonstrated that the proper functionalization of the surface layer of mesoporous silica can significantly enhance their adsorption efficiency.…”
Section: Adsorption Studiessupporting
confidence: 52%
“…Thus, the electrostatic interactions between the aforementioned groups and the silica surface are the main driving force for the adsorption (Shin et al 2012). This mechanism is dominant in the case of silica-based adsorbents, in contrast to the carbon-based adsorbents, where the hydrophobic interactions govern the adsorption process (Vinu et al 2006).…”
Section: Adsorption Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The compatibility of the pore diameter with the size of some proteins and enzymes controls their inclusion in the pores. 259,260 Thus, small size enzymes may penetrate into the nanometre size pores, while large enzymes are most likely immobilized in the large interparticle voids. 261 Adsorption of proteins inside the pores may be influenced by pH and ionic strength 262,263 or by the presence of heteroatoms in the silica framework.…”
Section: Functional Proteins and Enzymes Assembled To Silica And Silimentioning
confidence: 99%